Relationships of Zn between Centella asiatica and geochemical fractions of the habitat topsoils: implications of biomonitoring of Zn - Yap, Chee Kong; Omar, Hishamuddin; Nulit, Rosimah; Ong, Ghim Hock; Bakhtiari, Alireza A.; Varnamkhasti, Ali Karami; Al-Shami, Salman Abdo (Bentham Open, 2017)
Background:Present study focused on the relationships of Zn concentrations between Centella asiatica(leaves, stems and roots) and their habitat topsoils.Methods & Materials: For leaves, it is found that Zn levels in the leaves significantly (P< 0.05) correlated with geochemical fractions of easily, freely,leachable or exchangeable (EFLE) (R= 0.94), acid-reducible (AR) (R= 0.63), oxidisable-organic (OO) (R= 0.85), resistant (R) (R=0.79) and summation of all four fractions (SUM) (R= 0.83). For stems, it is found that Zn levels in the stems significantly (P< 0.05)correlated with AR (R= 0.73), R (R= 0.75) and SUM (R= 0.72). For roots, it is found that Zn levels in the roots significantly (P<0.05) correlated with EFLE (R= 0.88), AR (R= 0.65), OO (R= 0.86), R (R= 0.77) and SUM (R= 0.82).Conclusion: These results indicated that the three parts of C. asiatica are able to reflect the Zn concentrations in the habitat topsoils. Based on ecological risk (Er) of the habitat topsoils, all samplings sites were categorized as ‘Low potential ecological risk’ according to Hakanson classification. Based on the positive significant relationships of Zn concentrations between plant parts and geochemical fractions of their habitat topsoils, present study indicated that C. asiatica can be used as biomonitoring plant of Zn polluted topsoils.